Rational management of acute keratoconus - Yu. B. Slonimskiy; A. Yu. Slonimskiy; E. A. Korchuganova (Oftalʹmologiâ)
Acute keratoconus is a common and severe complication of advanced progressive keratoconus that occurs in more than 30 % of cases. Acute corneal edema in advanced progressive keratectasia is reffered to as acute corneal hydrops (hydrops corneae). It has been also reported in other ectatic disorders such as pellucid marginal degeneration. The most common misdiagnosis in hydrops is HSV disciform keratitis or acute bacterial keratitis. 126 corneal hydrops patients (79 men, 47 women) aged 16‑63 (129 eyes) were observed and treated over the last five years. 124 patients were diagnosed with acute keratoconus and 2 patients were diagnosed with pellucid marginal degeneration. Acute kereatoconus patientsrepresented a special and compromised cohort with systemic allergic diseases (neurodermatitis and various atopic disorders, n = 48), Down’s syndrome (n = 16) or mental disorders (n = 19). In many of these patients who vigorously rubbed their eyes, keratectasia progressed more rapidly. In 7 cases, acute keratoconus developed during pregnancy. 3 cases of recurrent keratoconus were reported — in a woman with Down’s syndrome (recurrence in 3 years), in a man with severe neurodermatitis (recurrence in 5 years), and in a man with anamnestic acute keratoconus (recurrence in 20 years). 3 patients experienced bilateral acute keratoconus. Acute keratoconus can be subdivided by the area of corneal edema into three categories, i.e., partial (6 mm or less, 52 eyes), subtotal (7‑10 mm, 56 eyes), and total (more than 10 mm, 21 eyes). Corneal edema ultimately disappeared, however, acute keratoconus resulted in a deep local scarring through the corneal layers. Slit lamp exam revealed Descemet’s membrane ruptures (so-called fish mouth). 73 eyes were referred to refractive penetrating keratoplasty (PKP). Corneal perforation was unusual even in severe corneal thinning (4 cases). In one case, descemetocele with a high risk of perforation was observed. 4 eyes required subtotal PKP. In one case, linear perforation was closed with interrupted sutures. Postoperative period following PKP was often complicated. Medical therapy which included topical steroids (eye drops and injections) in combination with antibiotics and drugs that promote corneal healing (Corneregel, Hylo-PARIN, VitA-POS) for 2‑3 months provided more rapid symptom relief and visual rehabilitation. There are many conflicting approaches to manage keratoconus. However, our long-term experience argues for PKP after complete symptoms relief excepting corneal perforation.